The Role of FinTech, Access to Digital Finance and Entrepreneurial Knowledge in Shaping Entrepreneurial Intentions: Evidence from Pakistan - Ali, Hafiz Mohsin; Saleem, Muhammad Waleed; Kamran, Hasan; Ateeq Ahmad (Minhaj International Journal of Economics and Organization Sciences, 2025)
This article investigates the influence of entrepreneurial expertise and financial technology (FinTech) on entrepreneurial intention. This article uses a quantitative data-gathering technique using a questionnaire to examine 250 business students from a public institution in Lahore. The main objective is to ascertain the effects of the independent variables, which are the role of Fintech, entrepreneurial knowledge and access to digital finance on the dependent variable entrepreneurial intention. Smart PLS 4 was used for the structural model analysis and measurement assessment model analysis, while SPSS was used for descriptive statistics and data analysis for this work. Descriptive statistics were employed to look into the characteristics of the sample population and Smart PLS was utilized to assess the correlations among the variables, reliability, validity, and test. The results of this article contribute to the body of research by illuminating how access to digital funding and entrepreneurial expertise impact business graduates' intention to pursue entrepreneurship. The results shed light on the usefulness of FinTech in encouraging entrepreneurial endeavors and underscore the need for entrepreneurship education in cultivating entrepreneurial intentions. Policymakers, educational institutions, and enterprises may find value in the results of this study. The establishment of an ecosystem that fosters entrepreneurship can be assisted by the development of policies and programs that increase access to digital currency. Courses on entrepreneurship and FinTech can be added to academic programs at educational institutions to give prospective graduates the knowledge and skills they need. Entrepreneurs can use fintech solutions to obtain capital and further their business objectives. To sum up, this thesis provides significant new understandings of the relationships among FinTech proficiency, access to digital money, and entrepreneurial intention. It has real-world implications for many interested parties in promoting entrepreneurship and using technology in the financial sector.